2021
DOI: 10.1097/acm.0000000000004121
|View full text |Cite
|
Sign up to set email alerts
|

The Content Quality of YouTube Videos for Professional Medical Education: A Systematic Review

Abstract: PurposeTo evaluate the content quality of YouTube videos intended for professional medical education based on quality rating tool (QRT) scores and determine if video characteristics, engagement metrics, or author type are associated with quality. MethodThe authors searched 7 databases for English-language studies about the quality of YouTube videos intended for professional medical education from each database's inception through April 2019. To be included, studies had to be published in 2005 (when YouTube was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 54 publications
4
43
0
Order By: Relevance
“…Despite being a very useful tool in the teaching-learning process, the quality of the contents of a video may vary depending on the target audience, the objectives and the sources of information/team that created the video. For example, in a systematic review on the content quality of medical education videos on the YouTube platform, it was found that there is a large number of videos with low quality scores and that the videos with the highest internal validity score were made by academic-physicians (23).…”
Section: Study Habits and Learning Sourcesmentioning
confidence: 99%
“…Despite being a very useful tool in the teaching-learning process, the quality of the contents of a video may vary depending on the target audience, the objectives and the sources of information/team that created the video. For example, in a systematic review on the content quality of medical education videos on the YouTube platform, it was found that there is a large number of videos with low quality scores and that the videos with the highest internal validity score were made by academic-physicians (23).…”
Section: Study Habits and Learning Sourcesmentioning
confidence: 99%
“…YouTube is the most popular media search and sharing platform globally, which has been widely utilized to search for and learn health information, especially in young adults [ 18 ]. Several studies have reported that people use YouTube as a source of health information to update knowledge, seek help before visiting hospitals, or even purchase healthcare services [ 19 , 20 ]. However, YouTube may contain misleading or poor-quality information due to the absence of any regulations or restrictions on video content for any uploader [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…YouTube is a favored place for students to watch and share videos, and the shift to online teaching during the COVID-19 pandemic has resulted in a further boost in its use among students [ 30 ]. Despite its potential as an instructional tool [ 31 ], the quality of YouTube videos intended for professional education has been under scrutiny [ 32 ] and this is mainly due to the lack of peer-review of the content before the online release of the videos. Video-based learning of endodontics is highly sought by students and the access cavity preparation step is the most in-demand.…”
Section: Discussionmentioning
confidence: 99%